Hymenopteran parasitoids as a biological control agent of potato tuber moth Phthorimaea operculella (Lepidoptera: Gelechiidae): A review (Bangladesh Journal of Zoology, 2025)
Potato tuber moth (PTM), Phthorimaea operculella Zeller (Lepidoptera: Gelechiidae) is the most destructive and cosmopolitan oligophagous pest of potato and many Solanaceous crops. Larvae damages potato leaves and tuber in both field and storage and causing significant yield losses. Chemical management of PTM through the use of pesticides is challenging, as the extensive application of these chemicals to control the pest leads to numerous health problems, destruction of beneficial organisms, and the development of insecticide resistance in pest populations. A safe and sustainable approach to pest control is to use parasitoid wasps as biological control agents. In this review, sixty-five species of parasitoid wasps of PTM under six families (Braconidae, Chalcididae, Encyrtidae, Eulophidae, Ichneumonidae and Trichogrammatidae) have been reported. Copidosoma koehleri (Hymenoptera: Encyrtidae), Apanteles subandinus (Hymenoptera: Braconidae), Orgilus lepidusa (Hymenoptera: Braconidae) have been  successfully introduced to control PTM worldwide. In warm environmental conditions, Trichogramma principium (Hymenoptera: Trichogrammatidae) is a better candidate for mass rearing and release as a biological control agent against PTM. Under favorable environmental conditions, successful parasitoid establishment is achievable through intercropping, combined releases of parasitoids from diverse families and sterile PTM, selective pesticide application, and improved mass rearing technologies. This review provides insights that can assist policymakers in making informed decisions for more effective pest management programs.Bangladesh J. Zool. 52(3): 185-195, 2024